Effect of the medial collateral ligament and the lateral ulnar collateral ligament injury on elbow stability: a finite element analysis. Issue 13 (3rd October 2021) - Wang, Fang; Jia, Shuoqi; Li, Mingxin; Pan, Kui; Zhang, Jianguo; Fan, Yubo
Abstract: Ligaments are the most important stabilizer of elbow. However, the stress of ligaments is hard to measure because of the complex biomechanical environment in the elbow. Our objective was to develop a human elbow finite element model and to validate it by a comparison with previous experimental data. Then several different ligaments injury conditions and elbow flexion were simulated to analyse the elbow instability and to stress the biomechanical consequences. The computational investigation of different effects of ligament constraints of elbow was studied by means of finite element analysis. The stress of the anterior bundle was almost greater than other ligaments in all conditions, which played the most important role during the elbow flexion. The posterior bundle was the secondary stabilizer during flexion after the anterior bundle. The lateral ulnar collateral ligament (LUCL) injury could result in an increase of the ulnar cartilage stress. The anterior bundle and the LUCL were recommended to be repaired in elbow joint dislocations and fractures. This study could help understand the dynamic effects of ligaments on the joint over the entire extension by investigating the tissue stress.